Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Impact of diagenesis and acidic alteration on microbial fabrics and trace element distributions in fossilised siliceous hot spring deposits - Barbara J. Lyon; Michael C. Rowe; Andrew Langendam; Kathleen A. Campbell; Diego M. Guido; Ayrton R. Hamilton; Ema E. Nersezova; Amanda Galar; Dominique A. Stallard (Geochimica et Cosmochimica Acta, 2026)

Estimating mercury exposure in amphibians using non-lethal tissue sampling - Caitlin T. Rumrill; Kelly L. Smalling; Colleen Emery; Blake R. Hossack; Brian J. Halstead; Michael J. Adams; Adam R. Backlin; Adrianne B. Brand; Jon M. Davenport; Robert N. Fisher; Jill Fleming; Brad M. Glorioso; et al. (Ecotoxicology, 2026)

Early intestinal barrier changes in A53T transgenic Parkinson’s disease mice - Myat Noe Han; Olivia Artaiz; Matthew C. Rowe; David I. Finkelstein; Shanti Diwakarla; Rachel M. McQuade (Cell and Tissue Research, 2026)
Gut dysfunction commonly precedes motor symptoms in Parkinson’s disease (PD), but the mechanistic sequence of gut versus brain pathology remains unclear. This work aimed to define the timing of intestinal barrier dysfunction relative to central nervous system (CNS) changes in the A53T α-synuclein transgenic mouse model of PD. Functional and molecular assessments of the gastrointestinal tract (ileum and colon) were conducted at 12 and 36 weeks. We measured in vivo and ex vivo intestinal permeability, nutrient absorption, histomorphology, goblet cell density, and expression of MUC2 and Claudin-1. Inflammatory markers (CRP, TNF-α, CD45) were quantified in plasma and gut tissues. A53T mice exhibited increased intestinal permeability at 12 and 36 weeks, with transiently elevated ex vivo transepithelial electrical resistance (TER) at 12 weeks. Nutrient absorption remained intact. Morphological changes included widened villi and crypts, altered mucin expression, and early reductions in Claudin-1 in the ileum and the colon while inflammatory markers remained largely unchanged. These findings suggest that gut dysfunction precedes known central pathology in A53T mice, supporting further investigation into the gut as an early site of pathology and a potential therapeutic target in PD.

Holocene hydroclimate inferred from alkane isotope and pollen records from monsoonal northern Australia - Michael I. Bird; Michael Brand; Rainy Comley; Xennephone Hadeen; Niels C. Munksgaard; Cassandra Rowe; Christopher M. Wurster; Costijn Zwart (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A new approach for assessing the radioecological risk associated with the legacy discharge of oil derived natural radioactivity in the UK North Sea - F. Dal Molin; D. Hunt; A. Dewar; S. Lozach; C. Phillips; B. Thomas; L. Warford; J.E. Parker; J. Walker; M. Chocholek; D.M. Paterson; H. Woodward-Rowe; et al. (Marine Pollution Bulletin, 2025)

Trace metal and organic biosignatures in digitate stromatolites from terrestrial siliceous hot spring deposits: Implications for the exploration of martian life - Ema E. Nersezova; Michael C. Rowe; Kathleen A. Campbell; Andrew Langendam; Cherie Tollemache; Barbara Lyon; Amanda Galar; Diego M. Guido; Bronwyn L. Teece; Trinity L. Hamilton (Chemical Geology, 2024)

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

A sulfur and halogen budget for the large magmatic system beneath Taupō volcano - Max S. Sharpe; Simon J. Barker; Shane M. Rooyakkers; Colin J. N. Wilson; Isabelle Chambefort; Michael C. Rowe; C. Ian Schipper; Bruce L. A. Charlier (Contributions to Mineralogy and Petrology, 2022)
The transport and degassing pathways of volatiles through large silicic magmatic systems are central to understanding geothermal fluid compositions, ore deposit genesis, and volcanic eruption dynamics and impacts. Here, we document sulfur (S), chlorine (Cl), and fluorine (F) concentrations in a range of host materials in eruptive deposits from Taupō volcano (New Zealand). Materials analysed are groundmass glass, silicic melt inclusions, and microphenocrystic apatite that equilibrated in shallow melt-dominant magma bodies; silicic melt and apatite inclusions within crystal cores inferred to be sourced from deeper crystal mush; and olivine-hosted basaltic melt inclusions from mafic enclaves that represent the most primitive feedstock magmas. Sulfur and halogen concentrations each follow distinct concentration pathways during magma differentiation in response to changing pressures, temperatures, oxygen fugacities, crystallising mineral phases, the effects of volatile saturation, and the presence of an aqueous fluid phase. Sulfur contents in the basaltic melt inclusions (~ 2000 ppm) are typical for arc-type magmas, but drop to near detection limits by dacitic compositions, reflecting pyrrhotite crystallisation at ~ 60 wt. % SiO 2 during the onset of magnetite crystallisation. In contrast, Cl increases from ~ 500 ppm in basalts to ~ 2500 ppm in dacitic compositions, due to incompatibility in the crystallising phases. Fluorine contents are similar between mafic and silicic compositions (< 1200 ppm) and are primarily controlled by the onset of apatite and/or amphibole crystallisation and then destabilisation. Sulfur and Cl partition strongly into an aqueous fluid and/or vapour phase in the shallow silicic system. Sulfur contents in the rhyolite melts are low, yet the Oruanui supereruption is associated with a major sulfate peak in ice core records in Antarctica and Greenland, implying that excess S was derived from a pre-eruptive gas phase, mafic magma recharge, and/or disintegration of a hydrothermal system. We estimate that the 25.5 ka Oruanui eruption ejected > 130 Tg of S (390 Tg sulfate) and up to ~ 1800 Tg of Cl, with potentially global impacts on climate and stratospheric ozone.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Trends of extreme air temperature and precipitation and their impact on corn and soybean yields in Nebraska, USA - Carlos A. C. dos Santos; Christopher M. U. Neale; Mesfin M. Mekonnen; Ivo Zution Gonçalves; Gabriel de Oliveira; Osias Ruiz-Alvarez; Babak Safa; Clinton M. Rowe (Theoretical and Applied Climatology, 2022)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

mGluR5 Allosteric Modulation Promotes Neurorecovery in a 6-OHDA-Toxicant Model of Parkinson’s Disease - Kyle Farmer; Khaled S. Abd-Elrahman; Alexa Derksen; Elyn M. Rowe; Ashley M. Thompson; Christopher A. Rudyk; Natalie A. Prowse; Zachary Dwyer; Samantha C. Bureau; Teresa Fortin; Stephen S.G. Ferguson; Shawn Hayley (Molecular Neurobiology, 2020)

Signaling from below: rodents select for deeper fruiting truffles with stronger volatile emissions - Ryan B. Stephens; Amy M. Trowbridge; Andrew P. Ouimette; W. Berk Knighton; Erik A. Hobbie; Paul C. Stoy; Rebecca J. Rowe (Ecology, 2020)
Many plant and fungal species use volatile organic compounds (VOCs) as chemical signals to convey information about the location or quality of their fruits or fruiting bodies to animal dispersers. Identifying the environmental factors and biotic interactions that shape fruit selection by animals is key to understanding the evolutionary processes that underpin chemical signaling. Using four Elaphomyces truffle species, we explored the role of fruiting depth, VOC emissions, and protein content in selection by five rodent species. We used stable isotope analysis of nitrogen (δ 15 N) in truffles to estimate fruiting depth, proton‐transfer‐reaction mass spectrometry to determine volatile emission composition, and nitrogen concentrations to calculate digestible protein of truffles. We coupled field surveys of truffle availability with truffle spore loads in rodent scat to determine selection by rodents. Despite presumably easier access to the shallow fruiting species, E. americanus (0.5‐cm depth) and E. verruculosus (2.5‐cm depth), most rodents selected for truffles fruiting deeper in the soil, E. macrosporus (4.1‐cm depth) and E. bartlettii (5.0‐cm depth). The deeper fruiting species had distinct VOC profiles and produced significantly higher quantities of odiferous compounds. Myodes gapperi (southern red‐backed vole), a fungal specialist, also selected for truffles with high levels of digestible protein, E. verruculosus and E. macrosporus . Our results highlight the importance of chemical signals in truffle selection by rodents and suggest that VOCs are under strong selective pressures relative to protein rewards. Strong chemical signals likely allow detection of truffles deep within the soil and reduce foraging effort by rodents. For rodents that depend on fungi as a major food source, protein content may also be important in selecting truffles.

Zones of influence for soil organic matter dynamics: A conceptual framework for data and models - Claudia Cagnarini; Eleanor Blyth; Bridget A. Emmett; Chris D. Evans; Robert I. Griffiths; Aidan Keith; Laurence Jones; Inma Lebron; Niall P. McNamara; Jeremy Puissant; Sabine Reinsch; David A. Robinson; et al. (Global Change Biology, 2019)
Soil organic matter (SOM) is an indicator of sustainable land management as stated in the global indicator framework of the United Nations Sustainable Development Goals (SDG Indicator 15.3.1). Improved forecasting of future changes in SOM is needed to support the development of more sustainable land management under a changing climate. Current models fail to reproduce historical trends in SOM both within and during transition between ecosystems. More realistic spatio‐temporal SOM dynamics require inclusion of the recent paradigm shift from SOM recalcitrance as an ‘intrinsic property’ to SOM persistence as an ‘ecosystem interaction’. We present a soil profile, or pedon‐explicit, ecosystem‐scale framework for data and models of SOM distribution and dynamics which can better represent land use transitions. Ecosystem‐scale drivers are integrated with pedon‐scale processes in two zones of influence. In the upper vegetation zone, SOM is affected primarily by plant inputs (above‐ and belowground), climate, microbial activity and physical aggregation and is prone to destabilization. In the lower mineral matrix zone, SOM inputs from the vegetation zone are controlled primarily by mineral phase and chemical interactions, resulting in more favourable conditions for SOM persistence. Vegetation zone boundary conditions vary spatially at landscape scales (vegetation cover) and temporally at decadal scales (climate). Mineral matrix zone boundary conditions vary spatially at landscape scales (geology, topography) but change only slowly. The thicknesses of the two zones and their transport connectivity are dynamic and affected by plant cover, land use practices, climate and feedbacks from current SOM stock in each layer. Using this framework, we identify several areas where greater knowledge is needed to advance the emerging paradigm of SOM dynamics—improved representation of plant‐derived carbon inputs, contributions of soil biota to SOM storage and effect of dynamic soil structure on SOM storage—and how this can be combined with robust and efficient soil monitoring.

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

Paleomagnetic determination of the age and properties of the 1780–1800 AD dome effusion/collapse episode of Mt. Taranaki, New Zealand - Geoffrey A. Lerner; Shane J. Cronin; Gillian M. Turner; Michael C. Rowe (Bulletin of Volcanology, 2019)

Gait stability in response to platform, belt, and sensory perturbations in young and older adults - S. Roeles; P. J. Rowe; S. M. Bruijn; C. R. Childs; G. D. Tarfali; F. Steenbrink; M. Pijnappels (Medical & Biological Engineering & Computing, 2018)

Incorporating linear programing and life cycle thinking into environmental sustainability decision-making: a case study on anchovy canning industry - I. Garcia-Herrero; J. Laso; M. Margallo; A. Bala; C. Gazulla; P. Fullana-i-Palmer; I. Vázquez-Rowe; A. Irabien; R. Aldaco (Clean Technologies and Environmental Policy, 2017)

Performance on the Cogstate Brief Battery Is Related to Amyloid Levels and Hippocampal Volume in Very Mild Dementia - Yen Ying Lim; Victor L. Villemagne; Simon M. Laws; Robert H. Pietrzak; David Ames; Christopher Fowler; Stephanie Rainey-Smith; Peter J. Snyder; Pierrick Bourgeat; Ralph N. Martins; Olivier Salvado; Christopher C. Rowe; et al. (Journal of Molecular Neuroscience, 2016)

Risk/Benefit Communication about Food—A Systematic Review of the Literature - L. J. Frewer; A. R. H. Fischer; M. Brennan; D. Bánáti; R. Lion; R. M. Meertens; G. Rowe; M. Siegrist; W. Verbeke; C. M. J. L. Vereijken (Critical Reviews in Food Science and Nutrition, 2016)

Empirical realised niche models for British coastal plant species - Susan G. Jarvis; Edwin C. Rowe; Peter A. Henrys; Simon M. Smart; Laurence Jones; Angus Garbutt (Journal of Coastal Conservation, 2016)

Groundmass crystallisation and cooling rates of lava-like ignimbrites: the Grey’s Landing ignimbrite, southern Idaho, USA - B. S. Ellis; B. Cordonnier; M. C. Rowe; D. Szymanowski; O. Bachmann; G. D. M. Andrews (Bulletin of Volcanology, 2015)

The benefit of offline sleep and wake for novel object recognition - Elizabeth A. McDevitt; Kelly M. Rowe; Mark Brady; Katherine A. Duggan; Sara C. Mednick (Experimental Brain Research, 2014)

A new synthesis of the molecular systematics and biogeography of honeyeaters (Passeriformes: Meliphagidae) highlights biogeographical and ecological complexity of a spectacular avian radiation - Leo Joseph; Alicia Toon; Árpád S. Nyári; N. Wayne Longmore; Karen M. C. Rowe; Tri Haryoko; John Trueman; Janet L. Gardner (Zoologica Scripta, 2014)
The passerine family Meliphagidae (the honeyeaters) comprises 175–180 species in 40–50 genera. It is an iconic element of the Australo‐Papuan avifauna and also occurs in Indonesia and on remote Pacific Ocean islands. Building on previous molecular studies that have pioneered a renewed understanding of the family's circumscription and systematics, we present an updated phylogenetic and systematics synthesis of honeyeaters derived from 112 mostly Australian, New Guinean and Wallacean species‐ and subspecies‐rank taxa aligned across 9246 positions spanning four mitochondrial and four nuclear genes. We affirm many of the recent changes advocated to the group's genus‐level systematics and offer some further refinements. The group's radiation appears to coincide broadly with the aridification of Australia in the Miocene, consistent with the time of origin of diversification of extant lineages in several other groups of Australian organisms. Most importantly, the complexity of the biogeography underlying the group's spectacular radiation, especially within Australia, is now apparent. Foremost among such examples is the robust evidence indicating that multiple, independent lineages of honeyeaters, including several monotypic genera, are endemic to the Australian arid zone, presumably having diverged and evolved within it. Also apparent and warranting further study are the phenotypic diversity among close relatives and the remarkably disjunct distributions within some clades, perhaps implying extinction of geographically intermediate lineages. Given such complexity, understanding the evolution of this radiation, which has thus far been intractable, relies on integration of molecular data with morphology, ecology and behaviour.

Cryptic genetic diversity in Rattus of the San Francisco Bay region, California - Chris J. Conroy; Kevin C. Rowe; Karen M. C. Rowe; Pauline L. Kamath; Ken P. Aplin; Lucia Hui; David K. James; Craig Moritz; James L. Patton (Biological Invasions, 2013)

Quantification of total and particulate dimethylsulfoniopropionate (DMSP) in five Bermudian coral species across a depth gradient - D. M. Yost; R. Jones; C. L. Rowe; Carys Louise Mitchelmore (Coral Reefs, 2012)

Size increase in high elevation ground squirrels over the last century - Lindsey M. Eastman; Toni Lyn Morelli; Kevin C. Rowe; Chris J. Conroy; Craig Moritz (Global Change Biology, 2012)
There is increasing evidence for morphological change in response to recent environmental change, but how this relates to fluctuations in geographic range remains unclear. We measured museum specimens from two time periods (1902–1950 and 2000–2008) that vary significantly in climate to assess if and how two high elevation contracting species of ground squirrels in the Sierra Nevada of California, Belding's ground squirrel ( Urocitellus beldingi ) and the golden‐mantled ground squirrel ( Callospermophilus lateralis ), and one lower elevation, stable species, the California ground squirrel ( Otospermophilus beecheyi ), have responded morphologically to changes over the last century. We measured skull length (condylobasal length), an ontogenetically more labile trait highly correlated with body size, and maxillary toothrow length, a more developmentally constrained trait predictive of skull shape. C. lateralis and U. beldingi , both obligate hibernators, have increased in body size, but have not changed in shape. In contrast, O. beecheyi , which only hibernates in parts of its range, has shown no significant change in either morphometric trait. The increase in body size in the higher elevation species, hypothesized to be a plastic effect due to a longer growing season and thus prolonged food availability, opposes the expected direction of selection for decreased body size under chronic warming. Our study supports that population contraction is related to physiological rather than nutritional constraints.

Impacts of atmospheric nitrogen deposition: responses of multiple plant and soil parameters across contrasting ecosystems in long‐term field experiments - Gareth K. Phoenix; Bridget A. Emmett; Andrea J. Britton; Simon J. M. Caporn; Nancy B. Dise; Rachel Helliwell; Laurence Jones; Jonathan R. Leake; Ian D. Leith; Lucy J. Sheppard; Alwyn Sowerby; Michael G. Pilkington; et al. (Global Change Biology, 2012)
Atmospheric nitrogen ( N ) deposition is a global and increasing threat to biodiversity and ecosystem function. Much of our current understanding of N deposition impacts comes from field manipulation studies, although interpretation may need caution where simulations of N deposition (in terms of dose, application rate and N form) have limited realism. Here, we review responses to simulated N deposition from the UKREATE network, a group of nine experimental sites across the UK in a diversity of heathland, grassland, bog and dune ecosystems which include studies with a high level of realism and where many are also the longest running globally on their ecosystem type. Clear responses were seen across the sites with the greatest sensitivity shown in cover and species richness of bryophytes and lichens. Productivity was also increased at sites where N was the limiting nutrient, while flowering also showed high sensitivity, with increases and declines seen in dominant shrub and forb species, respectively. Critically, these parameters were responsive to some of the lowest additional loadings of N (7.7–10 kg ha −1 yr −1 ) showing potential for impacts by deposition rates seen in even remote and ‘unpolluted’ regions of E urope. Other parameters were less sensitive, but nevertheless showed response to higher doses. These included increases in soil % N and ‘plant available’ KCl extractable N , N cycling rates and acid–base status. Furthermore, an analysis of accumulated dose that quantified response against the total N input over time suggested that N impacts can ‘build up’ within an ecosystem such that even relatively low N deposition rates can result in ecological responses if continued for long enough. Given the responses have important implications for ecosystem structure, function, and recovery from N loading, the clear evidence for impacts at relatively low N deposition rates across a wide range of habitats is of considerable concern.

Compositional and thermal evolution of olivine-hosted melt inclusions in small-volume basaltic eruptions: a “simple” example from Dotsero Volcano, NW Colorado - M. C. Rowe; D. W. Peate; A. Newbrough (Contributions to Mineralogy and Petrology, 2011)

Genetic analysis of avian influenza A viruses isolated from domestic waterfowl in live-bird markets of Hanoi, Vietnam, preceding fatal H5N1 human infections in 2004 - Samadhan J. Jadhao; Doan C. Nguyen; Timothy M. Uyeki; Michael Shaw; Taronna Maines; Thomas Rowe; Catherine Smith; Lien P. T. Huynh; Ha K. Nghiem; Diep H. T. Nguyen; Hang K. L. Nguyen; Hanh H. T. Nguyen; et al. (Archives of Virology, 2009)

A Genomewide Assessment of Inbreeding Depression: Gene Number, Function, and Mode of Action - JULIEN F. AYROLES; KIMBERLY A. HUGHES; KEVIN C. ROWE; MELISSA M. REEDY; SANDRA L. RODRIGUEZ‐ZAS; JENNY M. DRNEVICH; CARLA E. CÁCERES; KEN N. PAIGE (Conservation Biology, 2009)
Although the genetic basis of inbreeding depression is still being debated, most fitness effects are thought to be the result of increased homozygosity for recessive or partially recessive deleterious alleles rather than the loss of overdominant genes. It is unknown how many loci are associated with inbreeding depression, the genes or gene pathways involved, or their mode of action. To uncover genes associated with variation in fitness following inbreeding, we generated a set of inbred lines of Drosophila melanogaster for which only the third chromosome varied among lines and measured male competitive reproductive success among these lines to estimate inbreeding depression. Male competitive reproductive success for different lines validated our prediction that equally inbred lines show variation in inbreeding depression. To begin to assess the molecular basis of inbreeding depression for male competitive reproductive success, we detected variation in whole‐genome gene expression across these inbred lines with commercially available high‐density oligonucleotide microarrays. A total of 567 genes were differentially expressed among these inbred lines, indicating that inbreeding directly or indirectly affects a large number of genes: genes that are disproportionately involved in metabolism, stress and defense responses. Subsequently, we generated a set of outbred lines by crossing the highest inbreeding depression lines to each other and contrasted gene expression between parental inbred lines and F 1 hybrids with transcript abundance as a quantitative phenotype to determine the mode of action of the genes associated with inbreeding depression. Although our results indicated that approximately 75% of all genes involved in inbreeding depression were additive, partially additive, or dominant, about 25% of all genes expressed patterns of overdominance. These results should be viewed with caution given that they may be confounded by issues of statistical inference or associative overdominance.

Galantamine-induced improvements in cognitive function are not related to alterations in α4β2 nicotinic receptors in early Alzheimer’s disease as measured in vivo by 2-[18F]Fluoro-A-85380 PET - J. R. Ellis; P. J. Nathan; V. L. Villemagne; R. S. Mulligan; T. Saunder; K. Young; C. L. Smith; J. Welch; M. Woodward; K. A. Wesnes; G. Savage; C. C. Rowe (Psychopharmacology, 2009)

Abundance and demography of bottlenose dolphins in Dusky Sound, New Zealand, inferred from dorsal fin photographs - Rohan J. C. Currey; Lucy E. Rowe; Stephen M. Dawson; Elisabeth Slooten (New Zealand Journal of Marine and Freshwater Research, 2008)
The bottlenose dolphins ( Tursiops truncatus ) of Dusky Sound, Fiordland, New Zealand are a little‐studied group at the southern limit of the species range. Conducting a photo‐identification census and capture‐recapture analyses, we estimated there were 102 (CV = 0.9%) bottlenose dolphins in Dusky Sound during summer 2007/08, the first abundance estimate for this population. We did not encounter individuals from Doubtful Sound in Dusky Sound, suggesting little or no interchange between these neighbouring populations. Using a sex‐prediction model derived from laser‐metric photographs of dolphins in Doubtful Sound, we predicted the sexes of 79 individuals (98–99% of adults and sub‐adults) in Dusky Sound. Our predictions provided a sex ratio of 35 males to 44 females, not significantly different to a 1:1 ratio (G = 1.02, P > 0.05). High resighting rates of individual dolphins suggest the population may be resident, with dolphins observed throughout the entire fiord system.

Clonal dynamics in western North American aspen ( Populus tremuloides ) - K. E. MOCK; C. A. ROWE; M. B. HOOTEN; J. DEWOODY; V. D. HIPKINS (Molecular Ecology, 2008)
Clonality is a common phenomenon in plants, allowing genets to persist asexually for much longer periods of time than ramets. The relative frequency of sexual vs. asexual reproduction determines long‐term dominance and persistence of clonal plants at the landscape scale. One of the most familiar and valued clonal plants in North America is aspen ( Populus tremuloides ). Previous researchers have suggested that aspen in xeric landscapes of the intermountain west represent genets of great chronological age, maintained via clonal expansion in the near absence of sexual reproduction. We synthesized microsatellite data from 1371 ramets in two large sampling grids in Utah. We found a surprisingly large number of distinct genets, some covering large spatial areas, but most represented by only one to a few individual ramets at a sampling scale of 50 m. In general, multi‐ramet genets were spatially cohesive, although some genets appear to be fragmented remnants of much larger clones. We conclude that recent sexual reproduction in these landscapes is a stronger contributor to standing genetic variation at the population level than the accumulation of somatic mutations, and that even some of the spatially large clones may not be as ancient as previously supposed. Further, a striking majority of the largest genets in both study areas had three alleles at one or more loci, suggesting triploidy or aneuploidy. These genets tended to be spatially clustered but not closely related. Together, these findings substantially advance our understanding of clonal dynamics in western North American aspen, and set the stage for a broad range of future studies.

Evolution of biological dispersal corridors through a tectonically active mountain range in New Zealand - D. Craw; C. P. Burridge; P. Upton; D. L. Rowe; J. M. Waters (Journal of Biogeography, 2008)
Aim To assess the geological evolution and biogeographical implications of low mountain passes. In particular, we question the common biogeographical belief that major mountain belts form impervious physical barriers to biological dispersal, and that related taxa found on opposites sides of mountains are necessarily a result of vicariant tectonic processes. Location The Southern Alps of New Zealand form a long (500 km) narrow mountain belt at the oblique collisional Pacific–Australian tectonic plate boundary. High mountains were uplifted during the Pliocene (2–5 Ma) and uplift has continued to the present day. Methods We integrate previous work from several disciplines to obtain an overview of inter‐relationships between plate tectonic processes, geomorphology and biogeography along the main mountain barrier in New Zealand, and then extend this approach to other major mountain belts. Results The Southern Alps initially formed a barrier to at least some biological dispersal, including vicariant formation of separate species of freshwater non‐migratory galaxiid fish on either side. However, the high mountain barrier was breached in several places when passive transport of topography occurred, from the low‐erosion rain shadow on the eastern side towards the high‐erosion, high‐rainfall western side. This tectonic transport resulted in the capture of eastern rivers by west‐draining rivers, leaving low passes at the topographic divide. These low‐elevation corridors permitted biological dispersal across the mountains, although continued uplift raises these passes. A new set of passes has formed in the northern part of the mountains where younger faults are cutting across the older mountain topography. These potential dispersal corridors are becoming lower with continued erosion, and more common as the defining structures migrate southwards. Main conclusions Biological dispersal across the Southern Alps may be facilitated by numerous mountain passes, especially via the new passes formed by cross‐cutting faults. More low‐lying corridors existed than is readily apparent now, as old river capture‐related passes have been blocked by ongoing uplift. The dynamic mountain‐building and erosional environment typified by the Southern Alps occurs in all the world’s collisional mountain belts, such as the Andes, Himalayas, European Alps and North American Cordillera. Sister taxa occurring across mountain belts are not necessarily a result of vicariance driven by the rise of the mountains, as numerous passes may have permitted intermittent dispersal. The evolution of low passes may have been more prevalent than is currently appreciated, suggesting that topographically complex mountain ranges might be more effectively viewed as dynamic filters within a probability landscape rather than as static and impervious high‐altitude barriers to all but the rarest of biological dispersal events. In some cases, the biological disjunctions observed across mountains may more directly reflect habitat differentiation driven by orographic mountain development that has limited the probability of trans‐alpine dispersal success.

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Social and ecological factors affecting paternity allocation in American robins with overlapping broods - Karen M. C. Rowe; Patrick J. Weatherhead (Behavioral Ecology and Sociobiology, 2007)

Vegetation Type Affects the Relationship Between Soil Carbon to Nitrogen Ratio and Nitrogen Leaching - E. C. Rowe; C. D. Evans; B. A. Emmett; B. Reynolds; R. C. Helliwell; M. C. Coull; C. J. Curtis (Water, Air, & Soil Pollution, 2006)

Optimal mechanisms for finding and selecting mates: how threespine stickleback ( Gasterosteus aculeatus ) should encode male throat colors - M. P. Rowe; C. L. Baube; E. R. Loew; J. B. Phillips (Journal of Comparative Physiology A, 2004)

Seasonal profiles in growth, energy reserves, gonad development, and plasma steroids in age 1+ cultured Chinook salmon (Oncorhynchus tshawytscha) females - M. J. Unwin; C. W. Poortenaar; D. K. Rowe; N. C. Boustead; M. J. R. Porter (New Zealand Journal of Marine and Freshwater Research, 2004)
Sexual maturation in 2‐year‐old female Chinook salmon (Oncorhynchus tshawytscha) is unknown within their native range, but occurs in up to 20% of farmed stocks in New Zealand. To characterise the seasonal timing of oogenesis and subsequent ovarian development, we measured levels of plasma 17β‐estradiol and testosterone, condition factor, and gonadosomatic and hepatosomatic index, for freshwater‐reared female Chinook at 2–4‐week intervals during their second year of life (May 2001‐April 2002). These comprised two treatment groups under additional 24 h illumination from September to January, and two ambient controls. Macroscopic ovarian development first occurred in mid September (8 months before spawning), coinciding with detectable increases (≥0.3 ng ml ‐1 ) in both plasma steroids. Vitellogenesis was first observed in November and coincided with an increase in hepatosomatic index, possibly indicating the liver's role in transferring lipids to the developing ova. Neither mean weight nor the percentage of maturating fish (mean 6.9%) differed between the treatment and control groups at the end of the experiment, but ovarian development in the treatment group was advanced by 13 days relative to the controls. Reduced dark phase plasma melatonin levels confirmed that the additional light was sufficiently intense to produce a physiological response in the artificially illuminated fish.

Conserved simple sequence repeats for the Limnanthaceae (Brassicales) - V. K. Kishore; P. Velasco; D. K. Shintani; J. Rowe; C. Rosato; N. Adair; M. B. Slabaugh; S. J. Knapp (Theoretical and Applied Genetics, 2004)

Recovery ofVerticillium dahliae from North American certified seed potatoes and characterization of strains by vegetative compatibility and aggressiveness - M. A. Omer; D. A. Johnson; R. C. Rowe (American Journal of Potato Research, 2000)

Considerations on the use of video playbacks as visual stimuli: the Lisbon workshop consensus - R. F. Oliveira; G. G. Rosenthal; I. Schlupp; P. K. McGregor; I. C. Cuthill; J. A. Endler; L. J. Fleishman; J. Zeil; E. Barata; F. Burford; D. Gonçalves; M. Haley; et al. (acta ethologica, 2000)

Testing the safety-net role of hedgerow tree roots by 15N placement at different soil depths - E. C. Rowe; K. Hairiah; K. E. Giller; M. Van Noordwijk; G. Cadisch (Agroforestry Systems, 1998)

Elevated Trace Element Concentrations in Southern Toads, Bufo terrestris, Exposed to Coal Combustion Waste - W. A. Hopkins; M. T. Mendonça; C. L. Rowe; J. D. Congdon (Archives of Environmental Contamination and Toxicology, 1998)

Radiometric dating of the Middle Palaeolithic tool industry and associated fauna of Pin Hole Cave, Creswell Crags, England - Roger M. Jacobi; Peter J. Rowe; Mabs A. Gilmour; Rainer Grün; Timothy C. Atkinson (Journal of Quaternary Science, 1998)

Radiometric dating of the Middle Palaeolithic tool industry and associated fauna of Pin Hole Cave, Creswell Crags, England - Roger M. Jacobi; Peter J. Rowe; Mabs A. Gilmour; Rainer Grün; Timothy C. Atkinson (Journal of Quaternary Science, 1998)

Resistance exercise training and the orthostatic response - John P. McCarthy; Marcas M. Bamman; Janice M. Yelle; Adrian D. LeBlanc; Roger M. Rowe; Michael C. Greenisen; Stuart M. C. Lee; Elisabeth R. Spector; Suzanne M. Fortney (European Journal of Applied Physiology, 1997)

Influence of cultivar resistance toVerticillium SPP. On potato early dying - T. A. Wheeler; R. C. Rowe; R. M. Riedel; L. V. Madden (American Journal of Potato Research, 1994)

Lesion nematode involvement in potato early dying disease - Richard M. Riedel; Randall C. Rowe (American Journal of Potato Research, 1985)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

s 59th annual meeting Potato Association of America - D. E. Hudson; M. D. Volz; B. B. DePhillips; Gene A. Mathia; Frank Haynes; N. A. Wynn; Allen E. Abrahams; Lewis A. Schaper; Paul H. Orr; Earl C. Yaeger; Combs Joseph; Robert L. Mercer; et al. (American Journal of Potato Research, 1975)